2019
DOI: 10.15585/mmwr.ss6812a1
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Product Use and Associated Factors Among Middle and High School Students — 
United States, 2019

Abstract: Problem/ConditionTobacco use is the leading cause of preventable disease, disability, and death in the United States. Most tobacco product use begins during adolescence. In recent years, tobacco products have evolved to include various smoked, smokeless, and electronic products.Period Covered2019.Description of SystemThe National Youth Tobacco Survey (NYTS) is an annual, cross-sectional, school-based, self-administered survey of U.S. middle school (grades 6–8) and high school (grades 9–12) students. A three-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
411
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(480 citation statements)
references
References 15 publications
27
411
5
4
Order By: Relevance
“…One major challenge facing the FDA's anti-vaping campaign is the common perception among youth that vaping is a harmless activity (Kim et al, 2019b;Wang et al, 2019), a misconception perpetuated by tobacco-industry marketing (Huang et al, 2019).…”
Section: Participatory Strategies For Discouraging Youth Vapingmentioning
confidence: 99%
See 1 more Smart Citation
“…One major challenge facing the FDA's anti-vaping campaign is the common perception among youth that vaping is a harmless activity (Kim et al, 2019b;Wang et al, 2019), a misconception perpetuated by tobacco-industry marketing (Huang et al, 2019).…”
Section: Participatory Strategies For Discouraging Youth Vapingmentioning
confidence: 99%
“…In an attempt to disabuse teenagers of this "cost-free" mentality toward vaping (The U.S. Food Drug Administration, 2018a) 1 , the FDA campaign features images and videos of distorted faces and brains that are meant to reveal the real (but hard to see) detrimental health effects (The U.S. Department of Health Human Services, 2016American Cancer Society, 2017;Chung et al, 2018;Centers for Disease Control and Preventions, 2019;Gentzke et al, 2019;Wang et al, 2019) of e-cigarette consumption. Most of our focus-group participants found these images and videos repulsive and scary; however, seeing them did not motivate any e-cigarette users in our group (N = 4 of 8) to quit vaping.…”
Section: Participatory Strategies For Discouraging Youth Vapingmentioning
confidence: 99%
“…Additional limitations of the model include the focus on only two nicotine products (cigarettes and ecigarettes). Other products may alter the dynamics presented here, especially with cigar use surpassing cigarette use among youth (40). Similarly, the current policy was limited to overturning existing regulations (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…However, due to the unavailability of data, it was not possible to assess current or former HTP use status and related factors in the aforementioned study [ 13 ]. Dual or poly-tobacco use among adolescents is a public health problem [ 14 ]. In research conducted with US adolescents, the probability of HTP use among EC users was reported to be higher than among cigarette smokers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%